RESEARCH ON THE AWS LAMBDA PERFORMANCE FOR USER AUTHENTICATION IN CROSS-PLATFORM CLOUD APPLICATIONS - GUNCHENKO, Yurii; KAMIENIEVA, Alla; IEPIK, Maryna (Computer systems and information technologies, 2026)
The paper is devoted to investigating the effectiveness of using the serverless AWS Lambda architecture to implement a scalable user authorization system in a cloud environment. The authorization function is deployed as a cross-platform component that interacts with the managed Amazon Aurora PostgreSQL relational database and uses the AWS Systems Manager service to securely store configurations. The function’s performance depending on environment parameters (memory capacity, cold/warm start) was investigated, as well as the JWT token generation implementation for user identification. The results can be applied in the development of cloud applications focused on high scalability, portability, and secure database operations.